Tinospora cordifolia Silver Nanoparticles Attenuated the Lipopolysaccharide-induced Testicular Inflammation in Golden Hamster - Mishra N.K.; Yadav K.; Mohanty S.R.; Parmar A.S.; Yadav S.K.; Haldar C. (My University, 2025)
Purpose: Testicular inflammation is one of the primary causes of male infertility. Plant-rich remedies are known to reduce testicular inflammation, but the exact mechanism is not known. Tinospora cordifolia (T. cordifolia), an Indian ayurvedic medicinal plant, possesses excellent immunomodulatory properties. We therefore studied the anti-inflammatory potential(s) of green synthesized silver nanoparticles (AgNPs) from T. cordifolia (TC-AgNPs) on the testes of golden hamster. Methods: Aqueous extract of T. cordifolia was used to synthesize the silver nanoparticles (TC-AgNPs), validated by ultra-high-performance liquid chromatography-high-resolution accurate mass spectrometry (UHPLC-HRMS). Physical characterization was done using UV–Vis spectroscopy, transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), and Fourier transform infrared analysis (FTIR) spectroscopy. Biological parameters were measured using enzyme-linked immunosorbent assay (ELISA), western blot analysis, histopathology, photoacoustic, and ultrasound imaging. Results: The UV–Vis surface plasmon resonance (SPR) band at 420 nm confirmed the formation of TC-AgNPs. TEM revealed the semi-spherical morphology of silver nanoparticles with an average diameter of 15 nm. FTIR spectroscopy revealed the presence of multiple functional groups, indicating the bioformulation of silver nanoparticles with T. cordifolia extract. Biological studies with lipopolysaccharide (LPS) challenged male golden hamsters and demonstrated that TC-AgNPs treatment reduced the serum pro-inflammatory cytokine levels (IL-1β, IL-6, and TNF α). The testicular photoacoustic and ultrasound imaging indicated a significant improvement in testicular volume and oxygenation level. Western blot analysis suggests that TC-AgNPs reduced inflammation by downregulating NF-κB protein expression. Furthermore, TC-AgNPs alleviated LPS-induced testicular damages along with an increase in serum testosterone level. Conclusion: The synthesized TC-AgNPs have shown strong anti-inflammatory effects against LPS-induced testicular inflammation in male golden hamsters. Lay Summary: Medicinal plants are increasingly used to treat diseases, with inflammation being a common cause of male infertility. Phytoconstituents are safer and more effective anti-inflammatory agents than synthetic ones. Developing plant-based nanoformulations with high therapeutic efficacy and fewer side effects is essential. T. cordifolia is known for its strong immunomodulatory effects and was used to synthesize TC-AgNPs. Our study found that TC-AgNPs reduced pro-inflammatory cytokines and protected against LPS-induced testicular inflammation in golden hamsters. Further, TC-AgNPs improved testicular volume and oxygen saturation, demonstrating potent anti-inflammatory effects. Future Work/Prospective: Future research should focus on how individual bioactive compounds lower inflammation and explain the molecular mechanisms behind it. © The Author(s), under exclusive licence to The Regenerative Engineering Society 2024.